Profit Sharing dalam Pengelolaan Rumah Makan “Padang” - Fauzi Solihin (Bina Nusantara University, 2004)
Article discusses profit sharing in running a “Padang” restaurant. Profit sharing always increase sense of belonging every employee and support the management function. It can beconcluded that profit sharing can motivated employee to increase working performance and increase sense of belonging and responsibility. It also can increase continuous improvement team work between employee.